River life and the upspring of nature - Khan, Naveeda (Durham Duke University Press, 2023)
In River Life and the Upspring of Nature Naveeda Khan examines the relationship between nature and culture through the study of the everyday existence of chauras, the people who live on the chars (sandbars) within the Jamuna River in Bangladesh. Nature is a primary force at play within this existence as chauras live itinerantly and in flux with the ever-changing river flows; where land is here today and gone tomorrow, the quality of life itself is intertwined with this mutability.